2017
DOI: 10.1038/s41598-017-15021-4
|View full text |Cite
|
Sign up to set email alerts
|

A clinical-scale BioArtificial Liver, developed for GMP, improved clinical parameters of liver function in porcine liver failure

Abstract: Liver failure, whether arising directly from acute liver failure or from decompensated chronic liver disease is an increasing problem worldwide and results in many deaths. In the UK only 10% of individuals requiring a liver transplant receive one. Thus the need for alternative treatments is paramount. A BioArtificial Liver machine could temporarily replace the functions of the liver, buying time for the patient’s liver to repair and regenerate. We have designed, implemented and tested a clinical-scale BioArtif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 55 publications
0
38
0
2
Order By: Relevance
“…MSCs. [83,88,118,119]. Since in FLF the treatment need is immediate, and thus, the banking of these cell-products for the "on demand" access of patients has been extensively studied for two decades mostly with the use of slow freezing cryopreservation ( Table 5).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs. [83,88,118,119]. Since in FLF the treatment need is immediate, and thus, the banking of these cell-products for the "on demand" access of patients has been extensively studied for two decades mostly with the use of slow freezing cryopreservation ( Table 5).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…A similar study using cryopreserved microencapsulated porcine hepatocytes in FLF induced mice was also performed [123]. The Liver Group, from University College of London (UCL), is developing a bioartificial liver (7x10 10 cells biomass) for the treatment of FLF [83,88,125], studying for that aim, the slow freezing cryopreservation of alginate microencapsulated liver HepG2 spheroids [12,63,64,74,79,126,127]. To reduce contamination risks in the process, they compared a CRF without the use of liquid coolants with another CRF that use liquid nitrogen for slow cooling cryopreservation [126].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The BAL device has demonstrated improved outcomes in animal models of acute liver failure . Recently, phase I and II clinical trials have also confirmed that BAL exhibited significant improvement on prognostic clinical liver‐related parameters, suggesting the safety of BAL for human hepatocytes . However, there are many challenges on BAL systems, such as hepatocyte viability and the regulation of liver specific function, which lead to more limit of BAL systems for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently, phase I and II clinical trials have also confirmed that BAL exhibited significant improvement on prognostic clinical liver-related parameters, suggesting the safety of BAL for human hepatocytes. 7,8 However, there are many challenges on BAL systems, such as hepatocyte viability and the regulation of liver specific function, which lead to more limit of BAL systems for clinical treatment. Scaffold material is one of the major factors for the BAL system, which can supply a similar microenvironment for cells growth.…”
Section: Introductionmentioning
confidence: 99%